Accumulation of Chromium in Pak Choi (Brassica chinensis L.) Grown on Representative Chinese Soils. Issue 3 (1st May 2013) - Xiao, Wendan; Yang, Xiaoe; Zhang, Yibin; Rafiq, M. T.; He, Zhenli; Aziz, R.; Li, Tingqiang
Abstract : Anthropogenic chromium (Cr) pollution in soils poses a great threat to human health through the food chain. It is imperative to understand Cr accumulation properties in common vegetables because the proportion of vegetables consumed has increased with the improvement of living standards. This study investigated Cr accumulation in pak choi ( Brassica chinensis L.) grown on six representative agricultural soils in China. Chromium concentration in the edible parts of pak choi generally increased with soil Cr concentrations following the order: Ustic Cambosols > Periudic Argosols > Mollisols > Calcaric Regosols > Stagnic Anthrosols > Udic Ferrisols. Simple correlation analysis indicated that Cr concentration in pak choi was significantly correlated with the total Cr, Mehlich‐3–extractable Cr, and Cr(VI). Stepwise multiple regression analysis also demonstrated that the phytoavailability of Cr was strongly correlated with the extractable fraction by Mehlich‐3, total Cr concentration, soil organic matter, and Fe(II). Critical Cr concentrations in these six soils were evaluated for pak choi based on the maximum safe level for daily intake of Cr. Total soil Cr can be used as Cr thresholds for potential dietary toxicity in pak choi. Mehlich‐3–extractable Cr is most suitable to be used as Cr thresholds for Periudic Argosols, Udic Ferrisols, Mollisols, and Ustic Cambosols, with values of 20.7, 15.8, 21.2, and 20.4 mg kg −1, respectively, whereas Cr(VI) is most suitable for Calcaric Regosols and Stagnic Anthrosols, with values of 26.5 and 28.0 mg kg −1, respectively.